2017
DOI: 10.1155/2017/5863523
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Activities of Polysaccharides from Spent Mushroom Substrates (Laetiporus sulphureus) in Acute Alcohol‐Induced Mice

Abstract: In order to contribute to the exploitation and utilization of spent mushroom substrates (SMS) of Laetiporus sulphureus, hot-water-extractable polysaccharides (H-SMPS) and enzymatic-extractable polysaccharides (E-SMPS) were successfully isolated from SMS of L. sulphureus. Both H-SMPS and E-SMPS were found to have high reducing power and potential scavenging activities against hydroxyl, DPPH, and superoxide anion radicals. In vivo assays showed that the administration of H-SMPS and E-SMPS has potential hepatopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…GSH-Px specifically catalyzes the reduction reaction of GSH to peroxides to block the chain reaction of lipid peroxidation [ 39 ]. Therefore, increasing those enzymatic and nonenzymatic antioxidants may be conducive to relieve alcohol-induced oxidative stress [ 5 , 40 ]. The results of this study demonstrated that DOFE could reduce the level of MDA and increase the activity of SOD, CAT, and GSH-PX activities and the GSH level.…”
Section: Discussionmentioning
confidence: 99%
“…GSH-Px specifically catalyzes the reduction reaction of GSH to peroxides to block the chain reaction of lipid peroxidation [ 39 ]. Therefore, increasing those enzymatic and nonenzymatic antioxidants may be conducive to relieve alcohol-induced oxidative stress [ 5 , 40 ]. The results of this study demonstrated that DOFE could reduce the level of MDA and increase the activity of SOD, CAT, and GSH-PX activities and the GSH level.…”
Section: Discussionmentioning
confidence: 99%
“…The scavenging activity towards DPPH radical was measured according to the method reported by Zhao et al [25]. The mixture including AE-PS (0.2 mL, 0–400 μ g/mL) and DPPH solution (0.6 mL, 0.004%, w / v in methanol) was disposed at the dark and still standing for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For our experiment, the administration route, time of exposure, and dosage of the model established were decided by literature review, pre-experiments, and screens. One acute alcoholic liver injury model was established by the oral gavage route to cause mouse liver function loss so significant that it accords with human drinking habits, which avoided the shortcomings usually arising with intraperitoneal injections, such as organ adhesion, infection, and ascite formation (Wang et al, 2012;Zhao et al, 2017). However, the other acute liver injury model was induced by intraperitoneal CCl 4 injection of mice since the toxicant was absorbed quickly, and just one injection would bring an overall toxic response to animals.…”
Section: Discussionmentioning
confidence: 99%